Can we obtain low-dose and high quality images using 320-row multidedector computed tomography in paranasal sinus imaging? - Berhan Pirimoğlu; Recep Sade (Van Tıp Dergisi, 2018)
INTRODUCTION: To evaluate whether or not obtaining low-dose and high quality images in the paranasal sinus CT imaging using 320-row multidetector CT technique on phantom study. METHODS: Twenty phantom examinations were conducted with different settings of the tube voltage (135, 120, 100, 80 kV) and current. Dose measurements were derived from the study protocol as volume CT dose index (CTDIvol) and dose-length product (DLP). Image qualities of all the phantom images were assessed using a five-point scale (1: non-diagnostic to 5: excellent image quality) by observer 1 and 2. RESULTS: We obtained the lowest radiation dose in using 80 kVp and 2.5 mAs (CTDIvol: 0.2 mGy, DLP: 2.5 mGy x cm) phantom CT protocol and the highest radiation dose in using 120 kVp and 75 mAs (CTDIvol: 13.7 mGy, DLP: 191.2 mGy x cm) phantom CT protocol(p<0.001). We revealed the lowest radiation dose in using 135 kVp and 5 mAs (CTDIvol: 1.2 mGy, DLP: 16.9 mGy x cm) with high imaging quality for observer 1 and 2 (p<0.001). DISCUSSION AND CONCLUSION: We suggest that you can perform the 135 kVp and 5 mAs paranasal sinus CT protocol with high image quality in routine daily practice.